Interpersonal Communication of PAI Teachers in Forming Discipline and Responsibility Characters among for Childhood - Afkarina, Izza; Zuhri, Muhibbin (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2025)
Interpersonal communication has an important role in the educational process, especially in forming children's character. Islamic Religious Education (PAI) teachers have a big responsibility in educating and guiding children at school. Through effective interpersonal communication, PAI teachers can instill the values of discipline and responsibility in children. This research aims to examine the role of Islamic Religious Education (PAI) teachers' interpersonal communication in shaping the discipline and responsibility of middle childhood children at MI Islamiyah. This research uses a qualitative approach type case study research (case study). Research data uses primary and secondary data, data sources use informants, observations and documents. Data collection techniques use interviews, observation and documentation. The data was analyzed using the Miles and Huberman analysis method by condensing the data, presenting the data and drawing conclusions. Validation uses triangulation of sources, techniques and time. The results of this research show that PAI teachers' interpersonal communication in forming the character of discipline and responsibility in middle childhood children at MI Islamiyah has five ways, namely generating understanding, enjoyment, influence on attitudes, good relationships, and generating action